A cross-country comparison of dynamics in the large firm wage premium - Emanuele Colonnelli; Joacim Tåg; Michael Webb; Stefanie Wolter (Research Institute of Industrial Economics (IFN), 2018)
We provide stylized facts on the existence and dynamics over time of the large firm wage premium for four countries. We examine matched employer-employee micro-data from Brazil, Germany, Sweden, and the UK, and find that the large firm premium exists in all these countries. However, we uncover substantial differences among them in the evolution of the wage premium over the past several decades. Moreover, we find no clear evidence of common cross-country industry trends. We conclude by discussing potential explanations for this heterogeneity, and proposing some questions for future work in the area.
Keywords: E24; J01; J31; J33; 330; Dynamics; Large Firm Wage Premium